Liver allograft pathology: approach to interpretation of needle biopsies with clinicopathological correlation. Issue 1 (21st October 2009) - Adeyi, O; Fischer, S E; Guindi, M
Abstract : The spectrum of diseases encountered in post-transplant liver pathology biopsies is broad. In this review, these have been divided as belonging to one of three categories: (1) new-onset/de novo post-transplant abnormalities (early and late), (2) rejection, and (3) recurrence of original disease. The clinical and pathological features of the entities making up each category, with the relevant differential diagnosis and overlaps between and within these groups, are discussed and illustrated. Recurrent or de novo neoplasms make up a fourth category not included in this review. Early new-onset conditions are mostly related to surgical complications, donor factors and ischaemia to the graft. These include reperfusion/preservation injury, lipopeliosis, small-for-size-syndrome, biliary sludge syndrome and hepatic artery thrombosis. The various forms of rejection (cellular, chronic, antibody-mediated, and late atypical rejection) are detailed. Most chronic liver diseases can and do recur in the graft. They may display features that overlap with de novo conditions (eg, primary sclerosing cholangitis versus chronic rejection). As with most cases of allograft biopsy interpretation, accurate diagnosis rests with careful correlation of histological features with clinical, imaging and laboratory findings, and often comparison with previous sequential and follow-up biopsies. Late-onset new diseases include biliary strictures, idiopathic chronic hepatitis and de novo autoimmune hepatitis, among others. This review provides a practical approach to the interpretation of these challenging biopsies. Selected difficult scenarios or conundrums are identified and discussed in the relevant sections.